2022-RA-1309-ESGO Analysis of the prognostic value of systemic inflammation markers obtained from the complete blood count in patients treated for advanced ovarian carcinoma at the CUN in the period 2000–2015. (20th October 2022) - Jiménez, Jaime Espinós; Aramendía Beitia, José Manuel; Chacón, Matías Jurado; Mínguez Milio, José Ángel; Chiva, Luis; Eslava, Marta Santisteban; Villamayor, Julia; Lorenzo, Luisa Sánchez; Vazquez, Daniel; Castellanos, Teresa; Boria, Félix; Chacón, Enrique; et al.
Abstract : Introduction/Background: Markers of systemic inflammation have been described as prognostic factors in epithelial ovarian cancer (EOC). We aimed to retrospectively explore these new markers in our patient population and define its relationship with prognosis. Methodology: Medical records of patients with newly diagnosed FIGO stage III – IV EOC between 2000 and 2015 were reviewed. We examined the red cell distribution width (RDW), mean platelet volume (MPV), neutrophil to lymphocyte (NLR), monocyte to lymphocyte (MLR), and platelet to lymphocyte (PLR) ratios at diagnosis. Results: 77 patients were analyzed. Mean age 58.3 years. FIGO IIIC 56%, serous 87% (80% high grade). 69% had primary surgery, 47% optimal citorreduction. Relevant values at diagnosis: median RDW 13.7 (IQR 12.8 – 14.8), median MPV 8.6 fl (IQR 8.1 – 9.5), median NLR 3.4 (IQR 2.3 – 4–5), median MLR 0.3 (IQR 0.25 – 0.45), median PLR 217.5 (IQR 151.5 – 309.6). Survival analysis: Median PFS 21.8 months, CI95% 18.8 – 77.5. Median OS 74.4 months (CI95% 51.6 – 123.6). Multivariate Cox OS analysis: MLR≥0.245 was a risk factor for OS, HR 7.04, p=0.059 Univariate Cox PFS analysis: MLR at diagnosis >0.32 predicted worse PFS, 19.2 vs 31.7 months, p<0.001, HR 3.49. PLR at diagnosis >289.1 predicted worse PFS, 19.2 vs 24.8 months, p=0.01, HR 2. On multivariate PFS analysis none of the variables retained its significance. Conclusion: In our series, higher MLR at diagnosis predicted worse outcomes in FIGO III – IV patients.